2014
DOI: 10.5483/bmbrep.2014.47.5.166
|View full text |Cite
|
Sign up to set email alerts
|

Asn124 of Cel5A from Hypocrea jecorina not only provides the N-glycosylation site but is also essential in maintaining enzymatic activity

Abstract: To investigate the function of N-glycosylation of Cel5A (endoglucanase II) from Hypocrea jecorina, two N-glycosylation site deletion Cel5A mutants (rN124D and rN124H) were expressed in Saccharomyces cerevisiae. The weights of these recombinant mutants were 54 kDa, which were lower than that of rCel5A. This result was expected to be attributed to deglycosylation. The enzyme activity of rN124H was greatly reduced to 60.6% compared with rCel5A, whereas rN124D showed slightly lower activity (10%) than that of rCel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…To investigate whether the mannosyltransferase deletion also affect the secretion of non-glycosylated protein, we expressed a non-glycosylated protein, a N -glycosylation site mutation rCel5A (rN124D) of Trichoderma reesei endoglucanase Cel5A in the mannosyltransferase deletion strains 29 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether the mannosyltransferase deletion also affect the secretion of non-glycosylated protein, we expressed a non-glycosylated protein, a N -glycosylation site mutation rCel5A (rN124D) of Trichoderma reesei endoglucanase Cel5A in the mannosyltransferase deletion strains 29 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Cel3A gene with its native signal sequence and FLAG-tagged sequence was amplified from the plasmid pTH-BGL, the CelA gene with an INU1 signal sequence and myc-tagged sequence was amplified from pTH-CEL (37) and each gene was then ligated into the plasmid PYX242WS 42 under the control of the TPI1 promoter and the PGK1 terminator. The gene of Cel5A from T. reesei with a site mutation (rN124D) was amplified from recombinant plasmid pAJ401-cel5A-N124D 29 and inserted into plasmid PYX242WS. The yeast centromere plasmid pJFE1 containing the URA3 gene as a marker was used to over-express the genes RHO1 and PKC1 .…”
Section: Methodsmentioning
confidence: 99%
“…The removal of N-glycan at the N88 position of β-1,4-endoglucanase CTendo45 increased its catalytic activity toward CMC-Na and β- d -glucan; however, the addition of polysaccharides at the N65 position increased its catalytic activity [ 13 ]. In most cases, the lack of N-glycosylation reduces enzyme activity, which may be caused by changes in the secondary structure of the protein, as detected by circular dichroism analysis [ 14 ]. Conversely, recent studies have reported that the introduction of glycosylation sites increased enzyme activity.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile the deletion of N -linked glycans at the positions locating at the “bottom” of their catalytic domains resulted in a partial decrease of enzyme activity, because the glycan chains attaching to these residues could help the enzyme orient appropriately to the surface of cellulose microfibril. In most cases, the loss of N -linked glycosylation would reduce the enzyme activity, which was probably caused by the change of secondary structure via circular dichroism spectroscopy analysis [23]. Meanwhile it has been reported that the enzyme activity is increased by introducing glycosylation sites recently [18, 24].…”
Section: Introductionmentioning
confidence: 99%